Antihypertensive and analgesic/nonsteroidal antiinflammatory drug use by the elderly living in residential homes in Istanbul - (:unkn) unknown (My University, 2009)
OBJECTIVE: To assess the usage, knowledge and attitudes of elderly individuals living in residential homes in the Anatolian region of Istanbul, with particular reference to analgesic/nonsteroidal antiinflammatory drugs (NSAIDs) and antihypertensives. METHODS: This cross-sectional study was carried out with 247 representative individuals who were >or= 65 years old, and were living in residential homes in Istanbul. They scored >or= 24 in a Mini Mental Status Examination and were not suffering from speech, understanding or expression disorders, nor was any serious disease included in the study. Each medication that participants held, was recorded at sight. After asking about the dose, frequency, duration, purpose and side effects related with antihypertensives and analgesic/NSAIDs, the individual's weight, height and blood pressure were measured and activities of daily living and falling status were evaluated. RESULTS: 47% of the participants were male and the mean age was 76 +/- 7.2 years. 47% of the participants were using antihypertensives and 45% of them were using analgesic/NSAIDs. 30% of subjects who declared that they had hypertension were not on therapy. There was a statistically significant relationship between NSAID usage and having hypertension (p = 0.013, OR 2.064, 95% CI 1.16 - 3.65). 78 of the antihypertensive and 88% of the analgesic/NSAIDs users explained the purpose of the drug usage properly. However, only 9 and 18% were aware of the effects, respectively. CONCLUSIONS: Although these results suggest that regarding the antihypertensive and analgesic/NSAIDs administration, individuals were treated with proper drugs and doses, but a considerable number of old people are not sufficiently aware about their diseases and drugs.
Keywords: Female; Humans; Aged; Aged, 80 and over; Turkey; Cross-Sectional Studies; Male; Health Knowledge, Attitudes, Practice; Antihypertensive Agents; Anti-Inflammatory Agents, Non-Steroidal; Residential Facilities; Drug Utilization; Polypharmacy